2020
DOI: 10.1177/1120700020937952
|View full text |Cite
|
Sign up to set email alerts
|

Conversion total hip arthroplasty with a proximally modular, distal fixation reconstruction prosthesis following cephalomedullar nail failure

Abstract: Background: The goals of intertrochanteric hip fracture (IHF) treatment are stable fixation, early mobilisation and function restoration. If the attempt to reduce, stabilise and fracture healing utilising a femoral cephalomedullar nail (CMN) fails, options for subsequent attempts are limited. Purpose: Evaluate the clinical and radiographic outcomes of conversion total hip arthroplasty (THA) using a modular stem following a CMN failure. Materials and methods: We retrospectively reviewed a consecutive series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…No additional records were included. After screening for eligibility criteria, four articles were selected and included in this study (Figure 1) [24][25][26][27], and all reported on the outcomes and complications following conversion arthroplasty after femoral nail failure in intertrochanteric femoral fractures.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No additional records were included. After screening for eligibility criteria, four articles were selected and included in this study (Figure 1) [24][25][26][27], and all reported on the outcomes and complications following conversion arthroplasty after femoral nail failure in intertrochanteric femoral fractures.…”
Section: Search Resultsmentioning
confidence: 99%
“…The total amount of 483 cases included 476 conversion total hip arthroplasties and 7 conversion partial hip arthroplasties. The surgical approach used for the salvage procedure was not reported in two studies [25,26], while one reported a postero-lateral approach [27] and the other reported an extended direct lateral approach on previous scars [24]. The implant and type of fixation in revision surgery were reported at various levels of detail in each paper.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery is currently the preferred treatment protocol recommended for hip fracture patients ( 5 7 ). Internal fixation and artificial hip arthroplasty are the main surgical methods for hip fracture surgical treatment, and the advantages are not only reduced trauma and shortened bed time, but also significantly reduced the incidence of complications, promoted functional recovery of the hip joint and improved the life quality of hip fracture patients ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, proximal femur nail and hip arthroplasty are widely used in the treatment of hip fractures due to their suitability for various types of hip fractures, simple surgery, low blood loss, and low trauma ( 9 , 10 ). However, many clinical studies have compared the efficacy of proximal femur nail and hip arthroplasty in the treatment of hip fractures, but the results have been inconsistent or even opposite ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%